Analysis of Servqual and Demographic Aspects on Repurchase Intention Mediated by Customer Satisfaction of Ngaben Services at Hindu Crematoriums - Utama, Merta; Wimba, I Gusti Ayu; Sadiartha, Anak Agung Ngurah Gede (UNHI Press, 2024)
Purpose - This study aims to analyse the influence of service quality and demographic aspects on repurchase intention, mediated by customer satisfaction, in Hindu crematorium services. Methodology - The population of this study consisted of users of ngaben (Balinese cremation) service at Hindu crematorium. Samples were selected using simple random sampling. A questionnaire was distributed to 100 respondents. Data analysis method include descriptive analysis and inferential analysis using Structural Equation Model – Partial Least Square (SEM-PLS). Findings - The results shows that service quality and demographic aspects have positive and significant influence on customer satisfaction. Service quality and demographic aspects also have a positive and significant influence on repurchase intention. Customer satisfaction partially mediates the influence of service quality and demographic aspects toward repurchase intention. Originality – integrating service quality, demographic aspects, customer satisfaction and repurchase intention into a single study is rarely adopted research. This research can explain how demographic aspects (such as income and current residence) influence decision regarding ngaben at Hindu crematorium.